Declamped Piezoelectric Coefficients in Patterned 70/30 Lead Magnesium Niobate–Lead Titanate Thin Films. (18th January 2017) - Keech, Ryan; Ye, Linghan; Bosse, James L.; Esteves, Giovanni; Guerrier, Jonathon; Jones, Jacob L.; Kuroda, Marcelo A.; Huey, Bryan D.; Trolier‐McKinstry, Susan
Abstract : Lateral subdivision of blanket piezoelectric thin films increases the functional properties through both increased domain wall mobility and declamping of the intrinsic response. This work presents the local effects of substrate declamping on the piezoelectric coefficient d 33, f of 300 nm thick, rhombohedral, 001‐oriented lead magnesium niobate–lead titanate thin films at the 70/30 composition (70PMN–30PT). Films grown by chemical solution deposition on platinized Si substrates are patterned into strip structures ranging from 0.75 to 9 µm in width. The longitudinal piezoelectric coefficient, d 33, f, is interrogated as a function of position across the patterned structures by three approaches: finite element modeling, piezoresponse force microscopy, and nanoprobe synchrotron X‐ray diffraction. It is found that d 33, f increases from the clamped value of 40–50 to ≈160 pm V −1 at the free sidewall under 200 kV cm −1 excitation. The sidewalls partially declamp the piezoelectric response 500–600 nm into the patterned structure, raising the piezoelectric response at the center of features with lateral dimensions less than 1 µm (3:1 width to thickness aspect ratio). The normalized data from all three methods are in excellent agreement, with quantitative differences providing insight to the field dependence of the piezoelectric coefficient and its declamping behavior. Abstract : The longitudinal piezoelectric coefficient of patterned lead magnesium niobate–lead titanate thin films is interrogated as a function of position by three approaches: finite element modeling, piezoresponse force microscopy, and nanoprobe synchrotron X‐ray diffraction. Local property enhancements (≈3× increase) describe the spatial influence of declamping by free sidewalls and shape the roadmap of dimensional scaling for piezoelectric films.